Corrosion degradation of pipeline steels with different strength grades - Zvirko, O.I. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
Ukrainian gas mains steels, taking into account their age, are subjected to aging and degradation, which leads to deterioration of their properties, especially mechanical ones. Degradation of mechanical properties of steels is intensified by corrosion in the course of which hydrogen evolves and is absorbed by metal, so the metal becomes embrittled. The aim of this work is to define susceptibility of pipeline steels with different strength grades to corrosion degradation during their long-term service. The comparative studies of corrosion and electrochemical behaviour of low alloyed gas pipeline steels with different strength grades in NS4 aqueous solution, simulating soil environment, has been carried out. Pipeline steels with three strength grades in different states – in the as-received state and after long-term operation have been investigated. The influence of long-term operation on corrosion and electrochemical properties of steels has been analysed. It has been found that the 17H1S steel (steel is equivalent to X52 strength grade) is characterized by the lowest corrosion resistance among the studied steels, and the highest corrosion resistance is typical for the X70 steel in both studied states. Corrosion and electrochemical characteristics of pipelines steels with different strength grades in the NS4 environment have been significantly deteriorated due to long-term service. It has been found out that degree of corrosion degradation caused by long-term operation of gas mains is the highest for the high strength X70 steel. Electrochemical activation of pipeline steels caused by their long-term service comes out in an increase of cathode and anode processes intensity, increase of corrosion current density, decrease of polarization resistance and in a shift of corrosion potential values towards more negative ones for degraded steels compared with steels in the initial state.